2001
DOI: 10.1103/physrevlett.86.4714
|View full text |Cite
|
Sign up to set email alerts
|

Kruget al.Reply:

Abstract: Krug et al. Reply: In a Comment [1] on our recent Letter [2], Copel discusses features in our XPS data that had not been explained, presents new XPS and MEIS data, and questions the validity of the diffusion-reaction model that we proposed.The first point raised by Copel is the origin of the Si 2p photoelectron peak at 98.5 eV binding energy appearing in the analysis of Al 2 O 3 films on Si(001) after annealing in O 2 at 800 ± C for 30 s, which was unclear in our Letter [2]. Thickness inhomogeneities [1] shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
2
20
1
Order By: Relevance
“…O 2 annealing for 60 s ͑sample 3 in Table I͒ produces an increase on the O-areal density of about 30% with respect to the as-prepared sample ͑sample 1͒ and a comparable percentage decrease on the N-areal density. Figure 1͑b͒ shows Si, 16 [9][10][11][12][13] in aluminum, zirconium, and gadolinium oxides and silicates, the present HfO 2 /SiO x N y structure displays higher resistance to oxygen migration from the gas into the solid phase and incorporation therein, as well as smaller isotopic exchanges. 29 Si profiles were determined by NRP 16 ͑results not shown here͒, revealing that Si remains immobile during annealing, in contrast to several of the earlier mentioned materials where substrate Si is seen to migrate into the oxide film.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…O 2 annealing for 60 s ͑sample 3 in Table I͒ produces an increase on the O-areal density of about 30% with respect to the as-prepared sample ͑sample 1͒ and a comparable percentage decrease on the N-areal density. Figure 1͑b͒ shows Si, 16 [9][10][11][12][13] in aluminum, zirconium, and gadolinium oxides and silicates, the present HfO 2 /SiO x N y structure displays higher resistance to oxygen migration from the gas into the solid phase and incorporation therein, as well as smaller isotopic exchanges. 29 Si profiles were determined by NRP 16 ͑results not shown here͒, revealing that Si remains immobile during annealing, in contrast to several of the earlier mentioned materials where substrate Si is seen to migrate into the oxide film.…”
mentioning
confidence: 94%
“…Previous studies 1 in other high-k ultrathin films on Si indicated that the interface layer thickness and composition can vary according to the deposition method and routine, and various species can be transported during post deposition thermal processing, like oxygen, 9,10 Si, [11][12][13] and the metal species, 14,15 altering the atomic concentrations as well as chemical composition of the system and consequently electrical characteristics like dielectric constant, interface density of states, and mobility of charge carriers in the transistor channel. In particular, stability against annealing in O 2 -containing atmospheres is of high interest, since in further processing steps it is either performed intentionally to improve leakage current and CET characteristics 1,7,8 or unintentionally, because oxygen is almost always residual in any production furnace.…”
mentioning
confidence: 99%
“…The research enjoys accelerating interest [3,4], with an immense arsenal of complementary high sensitivity analysing techniques being applied in conjunction to explore microstructural, compositional, and bonding chemistry aspects of ultrathin (sub-5 nm) high-κ films on Si [5][6][7][8]. Applied techniques include medium-energy ion scattering (MEIS), high-resolution transmission electron microscopy (HRTEM), nuclear resonance profiling (NRP) and x-ray photoelectron and Auger spectroscopy.…”
mentioning
confidence: 99%
“…Therefore, one would in fact expect collinear coupling for arbitrary interface orientations. In another study, however, we found spinflop coupling for Fe 3 O 4 (001)/NiO [24]. In general, the (001)-interface is atomically compensated and spin-flop coupling should therefore occur quite naturally, but the lifting of the NiO sublattice degeneracy by the inverse spinel structure of the magnetite discussed above should suppress this type of coupling.…”
Section: Spin Axis Orientation Of the Antiferromagnetmentioning
confidence: 66%